background image

15.1. SECOND PRODUCT. OBLIQUE PRODUCT

257

Conjecture

1362

.

A ×

RLD

F

B

@

A

n

B

for some filters

A

,

B

.

A stronger conjecture:

Conjecture

1363

.

A ×

RLD

F

B

@

A

n

B

@

A ×

RLD

B

for some filters

A

,

B

.

Particularly, is this formula true for

A

=

B

= ∆

u ↑

R

]0; +

[?

The above conjecture is similar to Fermat Last Theorem as having no value

by itself but being somehow challenging to prove it (not expected to be as hard as

FLT however).

Example

1364

.

A

n

B

@

A ×

RLD

B

for some filters

A

,

B

.

Proof.

It’s enough to prove

A

n

B 6

=

A ×

RLD

B

.

Let ∆

+

= ∆

u ↑

R

]0; +

[. Let

A

=

B

= ∆

+

.

Let

K

= (

)

|

R

×

R

.

Obviously

K /

up(

A ×

RLD

B

).

A

n

B v↑

RLD

(Base(

A

)

,

Base(

B

))

K

and thus

K

up(

A

n

B

) because

FCD

(Base(

A

)

,

Base(

B

))

K

w

+

×

FCD

B

=

FCD

B

for

B

=]0; +

[ because for every

X

+

there is

x

X

such that

x

]0;

[ (for

every positive

) and thus ]

; +

[

⊆ h

K

i

{

x

}

so having

h

K

i

X

=]0; +

[

GR

+

×

FCD

B

X.

Thus

A

n

B 6

=

A ×

RLD

B

.

Example

1365

.

A ×

RLD

F

B

@

A ×

RLD

B

for some filters

A

,

B

.

Proof.

This follows from the above example.

Conjecture

1366

.

(

A

n

B

)

u

(

A

o

B

)

6

=

A ×

RLD

F

B

for some filters

A

,

B

.

(Earlier I presented a proof of the negation of this conjecture, but it was in

error.)

Example

1367

.

(

A

n

B

)

t

(

A

o

B

)

@

A ×

RLD

B

for some filters

A

,

B

.

Proof.

(based on [

8

]) Let

A

=

B

= Ω(

N

). It’s enough to prove (

A

n

B

)

t

(

A

o

B

)

6

=

A ×

RLD

B

.

Let

X

up

A

,

Y

up

B

that is

X

Ω(

N

),

Y

Ω(

N

).

Removing one element

x

from

X

produces a set

P

. Removing one element

y

from

Y

produces a set

Q

. Obviously

P

Ω(

N

),

Q

Ω(

N

).

Obviously (

P

×

N

)

(

N

×

Q

)

up((

A

n

B

)

t

(

A

o

B

)).

(

P

×

N

)

(

N

×

Q

)

+

X

×

Y

because (

x, y

)

X

×

Y

but (

x, y

)

/

(

P

×

N

)

(

N

×

Q

)

for every

X

up

A

,

Y

up

B

.

Thus some (

P

×

N

)

(

N

×

Q

)

/

up(

A ×

RLD

B

) by properties of filter bases.

Example

1368

.

(

RLD

)

out

(

FCD

)

f

6

=

f

for some convex reloid

f

.

Proof.

Let

f

=

A ×

RLD

B

where

A

and

B

are from example

1365

.

(

FCD

)(

A ×

RLD

B

) =

A ×

FCD

B

by proposition

1071

.

So (

RLD

)

out

(

FCD

)(

A ×

RLD

B

) = (

RLD

)

out

(

A ×

FCD

B

) =

A ×

RLD

F

B 6

=

A ×

RLD

B

.